2022
DOI: 10.1182/blood.2021012756
|View full text |Cite
|
Sign up to set email alerts
|

Diminished ovarian reserve in young women with sickle cell anemia

Abstract: Women with sickle cell anemia (SCA) have higher rates of diminished ovarian reserve (DOR) than age-matched controls. Pecker et al report a small study of patients with SCA that compares ovarian reserve in patients after stem cell transplant, on therapy with hydroxyurea (HU), and on supportive care. As expected, patients who received transplants have severe DOR. About one-third of patients on HU have DOR, while DOR was absent in patients on supportive care. Whether this reflects an impact of HU or is a biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…[46][47][48][49] Subfertility and premature ovarian failure in women with SCD could also account for lower pregnancy rates with older age; thus, studies on fertility preservation and non-gonadotoxic therapies for SCD should remain a high research priority. 10,46,50 Lastly, cumulative end-organ damage and decreased median survival may prematurely truncate the reproductive lifespan of women living with SCD. 3,4 Of note, we Primary C-section rates increased in Black women with SCD across each 10-year era of our study, though this increase did not significantly differ from that of primigravid Black women without SCD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48][49] Subfertility and premature ovarian failure in women with SCD could also account for lower pregnancy rates with older age; thus, studies on fertility preservation and non-gonadotoxic therapies for SCD should remain a high research priority. 10,46,50 Lastly, cumulative end-organ damage and decreased median survival may prematurely truncate the reproductive lifespan of women living with SCD. 3,4 Of note, we Primary C-section rates increased in Black women with SCD across each 10-year era of our study, though this increase did not significantly differ from that of primigravid Black women without SCD.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we included the Distressed Communities Index (DCI), which compares the economic well-being of communities across the US using a weighted average of seven populations-based metrics derived from zip code level data, then normalizes that value into a single summary statistic (or DCI score) ranging from 0 to 100. 42 We assigned each woman's DCI score based on her residential zip code at time of delivery as reported in the PDD or EDU, then categorized them into 1 of 5 predefined economic groups: prosperous (0-20), comfortable (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), mid-tier (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), at-risk (61-80), and distressed (81-100).…”
Section: Covariate Descriptionsmentioning
confidence: 99%
“…Women with SCD have multiple risks for reduced ovarian reserve: chronic inflammation, oxidative stress, and ovarian ischemia and reperfusion injuries ( 30 , 31 ). Three studies have demonstrated normal anti-mĂŒllerian hormone (AMH) levels in untreated adolescent and young adults with SCD ( 32 – 34 ). However, women with SCD experience a more rapid decline in ovarian reserve, with lower levels of AMH than age matched controls ( 33 , 35 , 36 ).…”
Section: Impact Of Hemoglobinopathies On Fertilitymentioning
confidence: 99%
“…However, women with SCD experience a more rapid decline in ovarian reserve, with lower levels of AMH than age matched controls ( 33 , 35 , 36 ). Females with SCD develop diminished ovarian reserve (DOR) at younger ages (25-30 years) than age-matched women ( 33 , 34 ). Yet, no studies to date define the definitive risk of infertility in this population ( 28 ).…”
Section: Impact Of Hemoglobinopathies On Fertilitymentioning
confidence: 99%
See 1 more Smart Citation